In Vivo Cellular and Molecular Imaging - Ahrens, Eric T. (Eric Thomas), 1965- (Current topics in developmental biology, 2005)
In recent times there has been an explosive expansion of new imaging methodologies that are capable of visualizing specific populations of cells and molecular events in vivo. Vital imaging enhances our ability to study animal models of human development and disease, such as cancers, cardiovascular disease, diabetes, and Alzheimer's. Furthermore, non-invasive imaging may ultimately be useful for monitoring new generations of clinical molecular and cellular therapeutics, such as those utilizing viral vectors and stem cells. These new capabilities have been facilitated by the development of new imaging probes or reagents that target specific cell types, are chemically responsive to physiology, or are responsive to the presence of specific molecules, such as nucleic acids or enzymes. This volume provides an introduction to some of the most exciting methods and applications of emerging non-invasive imaging technologies using magnetic resonance imaging (MRI), positron emission tomography (PET), and various biophotonic approaches. Highlighted, are recent developments in reagent design that impart unique abilities to these imaging modalities to elucidate biological processes in vivo. * Includes 9 chapters by expert researchers in the field of imaging * Introduces new methods and applications of non-invasive imaging technologies * Covers ermerging topics in imaging such as in vivo cell cancer cells, imaging of autoimmune diseases, and maganetic resonance imaging.